2016
DOI: 10.1002/cctc.201600806
|View full text |Cite
|
Sign up to set email alerts
|

A Fed‐Batch Synthetic Strategy for a Three‐Step Enzymatic Synthesis of Poly‐ϵ‐caprolactone

Abstract: A three‐step enzymatic reaction sequence for the synthesis of poly‐ϵ‐caprolactone (PCL) was designed running in a fed‐batch operation. The first part of the cascade consisted of two oxidation steps starting with alcohol dehydrogenase catalyzed oxidation from cyclohexanol to cyclohexanone and further oxidation to ϵ‐caprolactone (ECL) by means of a Baeyer–Villiger monooxygenase. As a third step, lipase‐catalyzed hydrolysis of the lactone to 6‐hydroxyhexanoic acid (6‐HHA) was designed. With this biocatalytic mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 24 publications
1
60
0
5
Order By: Relevance
“…Therefore, the data of one of our recently published results (Scherkus et al, 2016) shown in Figure 7 were taken into account. Therefore, the data of one of our recently published results (Scherkus et al, 2016) shown in Figure 7 were taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the data of one of our recently published results (Scherkus et al, 2016) shown in Figure 7 were taken into account. Therefore, the data of one of our recently published results (Scherkus et al, 2016) shown in Figure 7 were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Nomenclature a max maximum enzyme activity, mmol min À1 mL À1 (representing v max [mmol min À1 mg À1 ] multiplied by the enzyme concentration [mg mL À1 ]) a tot total maximum enzyme activity considering initial reaction volume (only simulation), mmol/min K ADH eq equilibrium constant for the ADH catalyzing the oxidation of CHL to CHN K X M Michaelis-Menten constant of compound X, mM k base rate constant of supplied volume by titration, L mmol À1 min À1 (k ECL divided by the molar concentration of NaOH [5 mol/L]) k ECL rate constant for lipase-catalyzed hydrolysis of ECL, min À1 k feed rate constant of supplied volume of CHL, L/min K ECL loss rate constant of uncatalyzed hydrolysisof ECL, min À1 K CHL loss rate constant of depletion of CHL, min À1 V reaction volume, L v feed feed rate of CHL, mmol/min Figure 6. Comparison of experimental and calculated data from the enhanced fedbatch synthesis of ECL and subsequent hydrolysis to 6-HHA (Scherkus et al, 2016). Conditions for calculation: V ¼ 0.05 L, a CHMO tot ¼ 28.5 mmol/min, a ADH;ox tot ¼ 518.5 mmol/min, a ADH;red tot ¼ 4229.4 mmol/min, k CHL loss ¼ 0.002 min À1 , v feed ¼ 19/ 20.4 mmol/min, k ECL loss ¼ 9.3 Á 10 À5 min À1 , k 0 ECL ¼ 0.004 L g À1 min À1 , [CALB] ¼ 0.5 g/L, k feed ¼ 1.9 Á 10 À6 /1.95 Á 10 À6 L/min, k base ¼ 8 Á 10 À6 L mmol À1 min À1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Realizing multi‐step reactions in one‐pot circumvents several purification steps and provides opportunities to reduce waste, time, and costs (Muschiol, Peters, Oberleitner, & Mihovilovic, ; Oberleitner et al, ; Schrittwieser, Velikogne, & Kroutil, ). In this context, several biocatalytic cascades have been designed to synthesize ϵ‐caprolactone starting from cyclohexanol, 2‐cyclohexen‐1‐ol, or hexane‐1,6‐diol (Bornadel, Hatti‐Kaul, Hollmann, & Kara, ; Mallin, Wulf, & Bornscheuer, ; Oberleitner, Peters, Rudroff, Bornscheuer, & Mihovilovic, ; Scherkus et al, ; Scherkus et al, ; Staudt, Bornscheuer, Menyes, Hummel, & Gröger, ). Recently, a biocatalytic reaction concept that mimicked chemical reaction route to synthesize lactones from cycloalkanes was designed by utilizing an in‐vitro cascade of four isolated enzymes (Pennec, Hollmann, Smit, & Opperman, ).…”
Section: Introductionmentioning
confidence: 99%